2016
DOI: 10.5539/jas.v8n6p137
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study on Effect of Silicon Application on Rice Blast Disease and Plant Morphology in Indonesia

Abstract: Si fertilizer was never used in rice cultivation by farmers in Indonesia. To evaluate the effect of Si application on blast disease, plant morphologies, and stomata formation on rice plant, a field experiment was conducted in West Java, Indonesia. Two treatments, Si+ (with 1000 kg·ha -1 of silica gel) and Si-(without Si application) were set in a randomized complete block design. The results showed that Si application in soil with high available Si 426 mg SiO 2 kg -1 significantly reduce leaf (p < 0.01) and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
2
1
1
Order By: Relevance
“…It probably indicated the adaptation of rice plant to water limited condition as reported by Spence et al (1986) and Kramer (1988). The present study showed that Si application clearly gave the positive effect on increasing stomata density on Ciherang variety throughout observation, which agreed with the previous results found in West Java (Siregar et al, 2016). These are in line with the result from Dias et al (2014), stated that there is indication of Si addition promoted the development of higher stomata density.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It probably indicated the adaptation of rice plant to water limited condition as reported by Spence et al (1986) and Kramer (1988). The present study showed that Si application clearly gave the positive effect on increasing stomata density on Ciherang variety throughout observation, which agreed with the previous results found in West Java (Siregar et al, 2016). These are in line with the result from Dias et al (2014), stated that there is indication of Si addition promoted the development of higher stomata density.…”
Section: Discussionsupporting
confidence: 83%
“…8, No. 12;2016 Si application clearly gave the positive effect on reducing leaf blast infection on Ciherang variety, which agreed with the research results found in West Java (Siregar et al, 2016) where soil Si available was 426.54 mg SiO 2 kg -1 and for the other rice varieties in different countries such as in Japan, Brazil and Thailand (Seebold, 1988;Prabhu et al, 2001;Hayasaka et al, 2005;Wattanapayapkul et al, 2011). The present result showed that Si application showed clearer effect on reducing blast disease on rice plant with soil Si available is 31.27 mg SiO 2 kg -1 , lower than critical level proposed by Dobermann and Fairhust (2000) 86 mg SiO 2 kg -1 .…”
Section: Discussionsupporting
confidence: 82%
“…The low rice yield at SiAP paddy soil status indicated the increased Si addition. In this study, the rice yield increase was not in line with Siregar et al (2016) in that adding exogenous Si could increase the growth and yield of paddy plants. This research shows that Si addition in paddy soils has potential to be implemented to increase the Si availability for paddy plants.…”
Section: Discussioncontrasting
confidence: 55%
“…However, it does not result in excessive yield loss if the infection occurs in the phase of tiller development. The use of Si application also indicated a positive effect to reduce the intensity of leaf and neck blast attack, in particular for Ciherang variety (Siregar et al 2016). Also, Amir et al (2003) reported that the blast neck might potentially damage the rice crop if there is ample moisture at the beginning of flowering; either happening in morning or afternoon.…”
Section: Hawar Daun Bakterimentioning
confidence: 98%